E-Discharge Planning Berbasis Teknologi Informasi untuk Meningkatkan Kualitas Hidup Pasien Tuberkulosis Paru - Mimi Jamilah (Journal of Telenursing (JOTING), 2023)
This study aims to determine the impact of using an electronic debit scheme. The method used is systematic data analysis by reviewing the results of the literature on the use of electronic release regimens to improve the quality of life in pulmonary tuberculosis (TB) patients. The study results show that a literature review of 10 selected journals and electronic discharge planning can improve the quality of life of pulmonary tuberculosis (TB) patients. In conclusion, an electronic patient plan can increase self-care knowledge, adopt a healthy lifestyle, and improve life quality. Keywords: Quality of Life, Patient Discharge Plan, Information Technology, Pulmonary Tuberculosis